Leydig Cell Tumor: A Case Report - Amatya, N; Zhu, M; Sapkota, PK (Nepalese Journal of Radiology, 2012)
Leydig cell tumor is a relatively uncommon tumor clinically presenting with gynecomastia, increased sex hormone levels (i.e. testosterone and estradiol) and other correlated symptoms. However, preoperative ultrasonic diagnosis is difficult especially when the clinical manifestations are unremarkable. We report a case of Leydig cell tumor of testis that presented with atypical features. NJR I VOL 2 I ISSUE 1 39-41 Jan-June, 2012 DOI: http://dx.doi.org/10.3126/njr.v2i1.6979